The Implementation of The Modernization of The Tax Administrative System on Taxpayer Compliance Personal Person - Feriadi Saludin (Golden Ratio of Taxation Studies, 2021)
The influence of implementing the modernization of the tax administration system is one of the government's efforts to increase taxpayer compliance. Changes made cover the areas of organizational structure, business processes and information and communication technology, human resource management, implementation of good governance and tax socialization. The purpose of this study was to determine the effect of modernization of the tax administration system on taxpayer compliance. The Pratama North Makassar Tax Service Office (KPP) was used as the research site by selecting Individual Taxpayers (WPOP) as the research sample. The sample used was 100 WPOP with cluster sampling technique. The data collection technique was carried out using a questionnaire. This study was tested using multiple linear regression analysis. Based on the results of the analysis it can be concluded that the variables of organizational structure, human resource management, good governance and tax socialization have a significant effect on taxpayer compliance. The human resource variable has a significant negative effect on taxpayer compliance at the Pratama North Makassar Tax Service Office (KPP).